OPTIMIZING ROTATIONAL ANGLE ASSESSMENT IN ACETABULAR FRACTURE THROUGH JUDET VIEW IN X-RAY IMAGING (Journal of Medical & Health Sciences Review, 2025)
Accurate assessment of acetabular fractures is crucial for effective treatment. The Judet view, a specialized X-ray projection, is essential for evaluating fracture morphology. However, inconsistent rotational angles during imaging can lead to inaccurate assessments. This study investigates the optimal rotational angle for Judet view X-ray imaging in acetabular fracture assessment. We analyzed 25 cases, comparing rotational angles of 10°, 20°, 30° and 45° to determine the most accurate angle for fracture visualization. Our results indicate that a 45° rotational angle provides the most reliable assessment of fracture morphology, improving inter-observer agreement and reducing measurement errors. Standardizing the Judet view X-ray protocol with this optimal angle can enhance diagnostic accuracy and inform treatment decisions for acetabular fractures. Our study analyzed 25 acetabular fracture cases, comparing Judet view X-ray images taken at rotational angles of 10°, 20°, 30° and 45o. We evaluated fracture visualization, inter-observer agreement, and measurement errors. This study demonstrates that optimizing the rotational angle in Judet view X-ray imaging significantly enhances the assessment of acetabular fractures. Our findings suggest that a 45° rotational angle provides the most accurate visualization of fracture morphology, improves inter-observer agreement, and reduces measurement errors.